Alterações na produtividade e composição nutricional de uma pastagem após segundo ano de aplicação de diferentes doses de cama de frango - Lana, Regina Maria Quintão; de Assis, Daniel Ferreira; de Andrade Silva, Adriane [UNESP]; Lana, Ângela Maria Quintão; Guimarães, Ednaldo Carvalho; Borges, Elias Nascentes (My University, 2010)
The objective was to evaluate the potential use of poultry litter, compared to mineral fertilization, productivity, features bromatologic and absorption of nutrients from a pasture of Brachiaria decumbens. The experimental area was installed in oxisoil in Uberlândia-MG. The design was randomized blocks with four replicates and the treatments used: control (without application of organic or mineral source), mineral fertilizer (60, 75 and 100 kg ha-1, P K, respectively); organic fertilization with poultry litter at rates of 3,125, 6,250, 9,375 and 12,500 kg ha-1. There were two cuts of the aerial part of Brachiaria decumbens, both at 60 days after treatment. We evaluated the yield of DM and the levels of CP, NDF, ADF, lignin, macro and micronutrients in shoots of grass. The results showed that application of poultry litter increased the productivity of DM and the levels of CP, N, P, K and Zn in Brachiaria decumbens. The poultry litter can be used as supplementary source of nutrients, the mineral fertilizer. The use of poultry litter not increased over the levels of S, Ca and Mg in Brachiaria decumbens.
Changes in productivity and nutritional composition of a pasture after the second year of implementation of different doses of poultry litter
Keywords: Farms residues; Organic fertilizer; Recycling of nutrients